Obituary John Henry (Jack) Curtis CB BE(Hons) BSc BA 1920–2013 - S. Wragge AM, Harry (Journal of Telecommunications and the Digital Economy, 2019)
Jack Curtis was born in Closeburn, near Brisbane on 20 September 1920.